Islamic healers: a legal study of the application of the common law and traditional and complementary medicine bill 2012 / Mohammed Badrulzzaman Abu Bakar...[et al.] - Abu Bakar, Mohammed Badrulzzaman; Che Had, Muhammad Afif; Wan Akil, Sharifah Shazzea; Ya'acob, Yusizreen Maslin (2013)
Islamic medicine is an alternative medicine treatment that has increased in popularity among the Muslims' patients in Malaysia. This treatment is provided by Darussyifa who also providing training for Islamic Medicine practitioner. This research looks into the law regulating Islamic medidne praetitioners in Malaysia. In United Kingdom Spiritual and Faith healing do not have any specific law regulating the practice but they have a very thorough code of conduct and their own disciplinary board. Any cases that are not within the scope the jurisdiction of this disciplinary board will be referred to the courts in United Kingdom. This research examined the different approaches of regulating alternative medicine practitioners under the common law and the Traditional and Complementary Bill 2012. It also identifies the problems and conflicts between the Bill and the Islamic Medreatpractitioner's code of conduct which is generally based on the Hukum Syarak.